1998
DOI: 10.1046/j.1365-313x.1998.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two methods of microinjection for assessing altered plasmodesmal gating in tissues expressing viral movement proteins

Abstract: SummaryUsing two different microinjection methods the effect of transgenic expression of the movement proteins (MPs) of tomato spotted wilt virus (TSWV) and tobacco mosaic virus (TMV) on plasmodesmal size exclusion limit (SEL) was assessed. By pressure mediated injection of fluorescent probes of different molecular mass, in both TSWV and TMV MP-transgenic tissues a similar enlargement of the plasmodesmal SEL was observed, in line with the general conception that alteration of plasmodesmal gating is an intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…The NSm protein of TSWV has typical characteristics of plant viral movement protein, including localization into plasmodesmata (PD) (Feng et al, 2016;Kormelink et al, 1994), modification of size-exclusion limit of PD (Prins et al, 1997;Storms et al, 1998), tubule formation (Storms et al, 1995), RNA-binding activity and interaction with N protein (Soellick et al, 2000). Using a heterologous Tobacco mosaic virus (TMV)-expression system, domains and amino-acid residues of the TSWV NSm protein necessary for tubule formation, intercellular movement and symptom †These authors contributed equally to this work.…”
Section: Tomato Spotted Wilt Virus (Tswv) Is the Type Species Ofmentioning
confidence: 99%
“…The NSm protein of TSWV has typical characteristics of plant viral movement protein, including localization into plasmodesmata (PD) (Feng et al, 2016;Kormelink et al, 1994), modification of size-exclusion limit of PD (Prins et al, 1997;Storms et al, 1998), tubule formation (Storms et al, 1995), RNA-binding activity and interaction with N protein (Soellick et al, 2000). Using a heterologous Tobacco mosaic virus (TMV)-expression system, domains and amino-acid residues of the TSWV NSm protein necessary for tubule formation, intercellular movement and symptom †These authors contributed equally to this work.…”
Section: Tomato Spotted Wilt Virus (Tswv) Is the Type Species Ofmentioning
confidence: 99%
“…The M RNA encodes a nonstructural cell-to-cell movement protein in v sense and the envelope glycoproteins (Gn and Gc) precursor in vc sense [6,7]. The L RNA differs from the other two genomic segments since it has a negative polarity and encodes a single ORF (protein L) with motifs found in RNA-dependent RNA polymerases (RdRp) [8].…”
Section: Introductionmentioning
confidence: 99%
“…This protein modifies the size exclusion limit of Pd (70,88,95) and binds nucleic acids in vitro, which led to the suggestion that the protein may chaperone vRNA to form a viral ribonucleoprotein (vRNP) complex whose size and structure are compatible with transport through the modified Pd (16,17). Studies to elucidate the pathway by which MP may target viral RNA to Pd have used MP in fusion with the green fluorescent protein (GFP) and shown that, in both plant cells and protoplasts, MP interacts with the cytoskeleton (32,57) and with elements of the endoplasmic reticulum (ER) (33,77).…”
mentioning
confidence: 99%